How to factor this trinomial 5x^2+3x-14?
- print Print
- list Cite
Expert Answers
calendarEducator since 2011
write244 answers
starTop subjects are Math, Science, and Literature
5x^2 + 3x - 14
First, set up your two binomials. Since the middle term is positive and the last term is negative, you know one of the binomials contains addition and the other binomial contains subtraction.
(___ + ___)(___ - ___)
The coefficient of the first term (5) is prime, so the first terms in the binomials are 5x and x.
(5x + ___)(x - ___)
The last term (-14) can be factored a few ways:
1, -14
14, -1
2, -7
7, -2
Now try out each combination. Using FOIL, find the combination that gives you the middle term 3x.
(5x + 1)(x - 14) middle term = 69x no
(5x + 14)(x - 1) middle term = 9x no
(5x + 2)(x - 7) middle term = -33x no
(5x + 7)(x - 2) middle term = -3x
That last combination was close, except we need the middle term to be postive 3x, not negative 3x. So we switch the + and - signs and try again.
(5x - 7)(x + 2) middle term = 3x
Use FOIL to check.
5x^2 + 10x - 7x - 14
5x^2 + 3x - 14
Since this was your original trinomial, it has been factored correctly.
Solution: (5x - 7)(x + 2)
Related Questions
- Solve by factoring: 3x^2 + 5x - 2 = 0.Solve by factoring. 1. x^2 + 5x + 6 = 0 2. 2x^2 - x - 3 =...
- 2 Educator Answers
- y=-3x+8 y=-5x-2
- 1 Educator Answer
- Write polynomial P as a product of linear factors : P(x) = 5x^3 -2x^2 + 5x - 2
- 2 Educator Answers
- Factor the expression by removing the common factor with the smaller exponent. 8x3(5x – 4)^(3/2)...
- 1 Educator Answer
- Find the domain f=(5x+4) / (x^2+3x+2)
- 1 Educator Answer
calendarEducator since 2010
write12,544 answers
starTop subjects are Math, Science, and Business
We have to factorize 5x^2+3x-14
5x^2+3x-14
=> 5x^2 + 10x - 7x - 14
=> 5x(x + 2) - 7(x + 2)
=> (5x - 7)(x + 2)
The factors of 5x^2+3x-14 = (5x - 7)(x + 2)
The trinomial could be factored if we know it's roots:
(x - x1)(x - x2), where x1 and x2 are it's roots.
To factor this trinomial, we'll apply the quadratic formula:
x1 = [-3+sqrt(3^2 - 4*5*(-14))]/2*5
x1 = (-3 + sqrt289)/10
x1 = (-3+17)/10
x1 = 14/10
x2 = (-3-17)/10
x2 = -20/10
x2 = -2
The factored form of the given trinomial is: (x - 14/10)(x + 2).
Student Answers